2012
DOI: 10.1021/jf300347p
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Advanced Glycation End Product Formation by Pu-erh Tea Ameliorates Progression of Experimental Diabetic Nephropathy

Abstract: Accumulation of advanced glycation end products (AGEs) has been implicated in the development of diabetic nephropathy. We investigated the effects of Pu-erh tea on AGE accumulation associated with diabetic nephropathy. Although it did not affect blood glucose levels and insulin sensitivy, Pu-erh tea treatment for 8 weeks attenuated the increases in urinary albumin, serum creatinine, and mesangial matrix in db/db mice. We found that Pu-erh tea prevented diabetes-induced accumulation of AGEs and led to a decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…PTE, green tea extract (GTE), and black tea extract (BTE) were kindly supplied by the China Academy of Pu-Erh Tea Research [21, 22]. These extracts were dissolved in distilled water and adjusted to pH 7.4 with 1 M NaOH.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PTE, green tea extract (GTE), and black tea extract (BTE) were kindly supplied by the China Academy of Pu-Erh Tea Research [21, 22]. These extracts were dissolved in distilled water and adjusted to pH 7.4 with 1 M NaOH.…”
Section: Methodsmentioning
confidence: 99%
“…A number of in vitro and animal studies have demonstrated that pu-erh tea has antioxidant [19] and antiobesity properties [20]. Pu-erh tea also has strong anticancer protective effects [21] and can ameliorate diabetic nephropathy [22]. Several compounds are produced during the postfermentation of pu-erh tea.…”
Section: Introductionmentioning
confidence: 99%
“…The use of many herbal medicines and experimental drugs has shown a reduction of AGE accumulation [49][50][51][52][53][54][55][56]. Also, many conventional drugs are useful in the reduction of AGE.…”
Section: Use Of Advanced Glycation End-products Reducing Drugsmentioning
confidence: 99%
“…Besides, alloxan (ALX) is another commonly used chemical agent to generate DN model to study the therapeutic effects of propolis (Orsolic, Sirovina, Koncic, Lackovic, & Gregorovic, 2012). Additional models for TCM edible plants studies are also available, such as db/db mice for Puerh tea, and KK-Ay mice for Averrhoa carambola (Yan et al, 2012;Zheng et al, 2013). The merits and drawbacks of these models are summarized and compared by Breyer in a specific review (Breyer et al, 2005).…”
Section: Experimental Dn Models Used In Tcm Edible Plants Studymentioning
confidence: 99%
“…Strikingly, grape seed proanthocyanidins showed a pronounced therapeutic effect on experimental DN through multiple cellular targets (Cheng et al, 2007;Li et al, 2009;Liu, Shen, & Yao, 2006;Mansouri et al, 2011). Furthermore, the formation of AGEs was inhibited in db/ db mice after treatment with Pu-erh tea (Yan et al, 2012). Green tea has been well documented for its protective effects in experimental diabetes, which involve a complex mechanism ( Additionally, soybeans and soy foods also have similar effects (Anderson, Smith, & Washnock, 1999).…”
Section: Bioactive Components From Tcm Edible Plantsmentioning
confidence: 99%